Preoperative platelet transfusions to reverse antiplatelet therapy for urgent non‐cardiac surgery: an observational cohort study. (28th February 2018) - Baschin, M.; Selleng, S.; Hummel, A.; Diedrich, S.; Schroeder, H. W.; Kohlmann, T.; Westphal, A.; Greinacher, A.; Thiele, T.
Abstract : Essentials An increasing number of patients requiring surgery receive antiplatelet therapy (APT). We analyzed 181 patients receiving presurgery platelet transfusions to reverse APT. No coronary thrombosis occurred after platelet transfusion. This justifies a prospective trial to test preoperative platelet transfusions to reverse APT. Summary: Background: Patients receiving antiplatelet therapy (APT) have an increased risk of perioperative bleeding and cardiac adverse events (CAE). Preoperative platelet transfusions may reduce the bleeding risk but may also increase the risk of CAE, particularly coronary thrombosis in patients after recent stent implantation. Objectives: To analyze the incidence of perioperative CAE and bleeding in patients undergoing non‐cardiac surgery using a standardized management of transfusing two platelet concentrates preoperatively and restart of APT within 24–72 h after surgery. Methods: A cohort of consecutive patients on APT treated with two platelet concentrates before non‐cardiac surgery between January 2012 and December 2014 was retrospectively identified. Patients were stratified by the risk of major adverse cardiac and cerebrovascular events (MACCE). The primary objective was the incidence of CAE (myocardial infarction, acute heart failure and cardiac troponine T increase). Secondary objectives were incidences of other thromboembolic events, bleedings, transfusions and mortality. Results: Among 181 patients, 88 received aspirin, 21 clopidogrel and 72 dual APT. MACCE risk was high in 63, moderate in 103 and low in 15 patients; 67 had cardiac stents. Ten patients (5.5%; 95% CI, 3.0–9.9%) developed a CAE (three myocardial infarctions, four cardiac failures and three troponin T increases). None was caused by coronary thrombosis. Surgery‐related bleeding occurred in 22 patients (12.2%; 95% CI, 8.2–17.7%), making 12 re‐interventions necessary (6.6%; 95% CI, 3.8–11.2%). Conclusion: Preoperative platelet transfusions and early restart of APT allowed urgent surgery and did not cause coronary thromboses, but non‐thrombotic CAEs and re‐bleeding occurred. Randomized trials are warranted to test platelet transfusion against other management strategies.